Research on the fuzzy evaluation of the livability of old urban communities using an analytic hierarchy process – a case study of Nanjing city in China. Issue 2 (3rd June 2021) - Wang, Xiaoxiao; Shi, Ruiting; Wang, Ting
Abstract : Purpose: Due to the different actual construction conditions in different cities, the requirements for community livability may also differ due to different geographical locations and urban construction priorities. The research system in this paper can be applied to study similar old communities in old urban areas. The indicator system would need to be adjusted in different places, based on specific construction situations and higher planning requirements. This process would provide valuable insights for effective construction projects that support the livability of the old communities. Design/methodology/approach: Based on sustainable and people-oriented development principles, this study considered the development of old urban communities during today's rapid urban renewal and development. Using previous literature and related research experience, this study established an evaluation indicator system to assess the livability of old urban communities. Based on the local resident experience and satisfaction, the study investigated current weaknesses in the construction of livable old urban communities and developed corresponding recommendations for reform based on these. The goal was to provide guidance and recommendations for renewing old communities in during urban development and further promote the sustainable development of the city. Findings: Based on the people-oriented principle and focusing on old urban communities as the research object, this study constructed an evaluation indicator system to evaluate the livability of urban old communities. The goal was to identify the weaknesses in the construction of old urban communities, with a focus on livability. Using the Bei'anmen community in Nanjing as a case study, the AHP method and fuzzy comprehensive evaluation method were applied to evaluate the overall target level and specific indicators, with the goal of assessing the level of livability in the Bei'anmen community.[AQ2] The results show that the livability of the Bei'anmen community is "very poor, " with significant room for improvements in community livability. This study also proposed corresponding measures for improving problems related to livability in the old urban community. Establishing the indicator system may help evaluate the livability of similar old communities in Nanjing and the same types of old communities in other cities. Understanding the overall livability of communities under construction can help identify weaknesses in other own construction approaches and may inform appropriate steps to improve the sustainable construction of the community in the wave of continuous urban renewal. This may realize the further development of livability in the community. Originality/value: The community is an integral part of the city and strengthening the community's civilization can support a harmonious and stable social environment. In constructing livable communities, improving the community civilization can promote social progress and civilization, promote social harmony and support the harmonious and sustainable development of communities. To strengthen the construction of a livable community, it is important to apply a residential perspective and provide a good platform for managing community participation and interaction. This may include organizing community-level cultural activities and strengthening communication between residents to increase the residents' affection for the community. This would enhance the residents' sense of belonging, forming a harmonious and stable atmosphere of community life, mutual help and mutual tolerance.